Menilik Keharmonisan Keluarga Kristen: Menakar Ego dan Membangun Kesatuan Secara Teologis - Romelus Blegur (Sekolah Tinggi Teologi Aletheia, 2025)
Harmony in the family is an ideal principle in building a household, but this principle is not easy in practice due to various factors, one of which is the problem of ego. The aim of this research is to examine the influence of ego in the turmoil of Christian family life, which on the one hand can create disharmony, nevertheless on the other hand can create harmony. This depends on how to measure ego so that harmony is created among family members. The theological perspective is used in this research as a lens for solving the problem of family harmony. The method used is literature method through analyzing the text according to the research problem. The results of the research shows that ego plays an important role in building family harmony, nevertheless it must be based on theological awareness about the Christian family. However, the ego’s vulnerability to bad influences can harm family harmony, so it must be measured properly to create balance between family members. This can be established through good communication relationships, as well as loving relationships between family members that are based on God’s love.